2023
DOI: 10.1111/pce.14549
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of cuticular wax biosynthesis mediated by rice LOV KELCH REPEAT PROTEIN 2 supports a negative role in drought stress tolerance

Abstract: Drought tolerance is important for grain crops, including rice (Oryza sativa); for example, rice cultivated under intermittent irrigation produces less methane gas compared to rice grown in anaerobic paddy field conditions, but these plants require greater drought tolerance. Moreover, the roles of rice circadian-clock genes in drought tolerance remain largely unknown. Here, we show that the mutation of LOV KELCH REPEAT PROTEIN 2 (OsLKP2) enhanced drought tolerance by increasing cuticular wax biosynthesis. Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…sphingolipids) and may also be stored in oil bodies as triacylglycerol (TAG). Being the precursors of cutin and wax, VLCFAs play important roles in plant responses to abiotic and biotic stress (reviewed in Batsale et al., 2021), with wax biosynthesis recently shown to improve drought tolerance in rice (Shim et al., 2023). On the other hand, phosphatidic acid (PA), an intermediate of lipid biosynthesis and important signalling molecule in plants (reviewed in Yu et al., 2017) may also contribute to improved stress responses in the transgenic lines.…”
Section: Discussionmentioning
confidence: 99%
“…sphingolipids) and may also be stored in oil bodies as triacylglycerol (TAG). Being the precursors of cutin and wax, VLCFAs play important roles in plant responses to abiotic and biotic stress (reviewed in Batsale et al., 2021), with wax biosynthesis recently shown to improve drought tolerance in rice (Shim et al., 2023). On the other hand, phosphatidic acid (PA), an intermediate of lipid biosynthesis and important signalling molecule in plants (reviewed in Yu et al., 2017) may also contribute to improved stress responses in the transgenic lines.…”
Section: Discussionmentioning
confidence: 99%
“…OsLKP2 interacts with OsGI and negatively regulates wax accumulation on the surface of rice leaves, reducing the recovery ability of rice to drought stress. The cuticular wax content of oslkp2 or osgi mutants increases, thus enhancing their drought tolerance [125]. OsCHR4 regulates cuticular wax formation by epigenetically regulating the expression of wax biosynthesis genes.…”
Section: Regulation Of Cuticular Wax Depositionmentioning
confidence: 99%
“…The null mutations of OsLKP2 displayed enhanced drought tolerance by increasing cuticular wax biosynthesis, which subsequently inhibited nonstomatal water loss. Furthermore, it was found that OsLKP2 could physically interact with another clock component, OsGI, in the nucleus, and the null mutation of OsGI also showed enhanced drought tolerance with a high density of wax crystals, suggesting that the interaction of OsGI and OsLKP2 negatively regulates wax accumulation to decrease rice resilience to drought stress [49] (Figure 4). This evidence jointly suggests that rice clock components are important for regulating drought tolerance, either in ABA-dependent or ABA-independent pathways.…”
Section: Crop Circadian Clock Components Regulate Drought Stressmentioning
confidence: 99%